TINGKAT ADOPSI TEKNOLOGI SISTEM JAJAR LEGOWO PADI SAWAH DI KECAMATAN CIGASONG KABUPATEN MAJALENGKA - Lukman Effendy; Siska Dinia Pratiwi (Politeknik Pembangunan Pertanian Medan, 2020)
Jajar Legowo (Jarwo) planting system technology has been known by farmers since the early 2000s. But in the field its application by farmers is not satisfactory because there are still many farmers who have not yet applied their paddy field, so this study aims: (1) to describe the level of adoption of jarwo paddy by farmers and (2) analyze the factors that influence the adoption of jarwo. The study was conducted in March until June 2018 in Cigasong Subdistrict, Majalengka Regency. Data were collected through direct observation and interviews with 65 farmers from a population of 178 farmers, using a closed questionnaire. Data analysis was carried out descriptively to explain the role of the selected variables, then to identify factors related to the level of adoption the Spearman rank analysis was performed, and to determine the ranking of counseling material was done Kendall's W. Concordance Analysis The results showed: (1) most respondents (77.5%) were in the medium category in the adoption of jarwo technology, (2) external factors consisting of information sources, extension activities, and the nature of innovation showed a significant relationship to the adoption of jarwo, while internal factors that are age, level of education and land area, show no real relationship.